KINDS AND FUNCTIONS OF CONSTATIVE ILLOCUTIONARY ACTS EXPRESSED IN THE UTTERANCES OF NOVEL’S CHARACTERS - Vivi Amelia; I Nyoman Kardana; I Gusti Ngurah Adi Rajistha (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2018)
The aims of this paper is to describe the illocutionary act especially the kinds and the functions of constative illocutionary acts. Qualitative approached was applied in this research. The data were taken from novel written by Soman Chainani. All the data were collected based on the utterance uttered by the characters in the novel. In the other words, the data were classified based on their kinds and functions. Meanwhile in presenting the result this paper used informal methods. After analyzing the data based on the Bach and Harnis’ theory, it can be concluded all the kinds of constative illocutionary act were found in the novel. Most of the kinds use specific verbs as the marker of the kinds and some others have the same meaning without marking verbs. The functions of constative illocutionary act are to declare something, to predict an event, to recount an event from the past, to report the rumor, to describe someone physically, to provide an information, to inform the news, to confirm something, to confess something, to retract unreliable utterance, to agree with someone proposition, to disagree with someone’s thought, to dispute an assumption, to answer someone’s question, to give suggestion to others and to guess the possibility of something.